Cryptanalysis of an Authenticated Key Agreement Protocol for Wireless Mobile Communications - He, Debiao (ETRI journal, 2012)
With the rapid progress of wireless mobile communications, the authenticated key agreement (AKA) protocol has attracted an increasing amount of attention. However, due to the limitations of bandwidth and storage of the mobile devices, most of the existing AKA protocols are not suitable for wireless mobile communications. Recently, Lo and others presented an efficient AKA protocol based on elliptic curve cryptography and included their protocol in 3GPP2 specifications. However, in this letter, we point out that Lo and others’ protocol is vulnerable to an offline password guessing attack. To resist the attack, we also propose an efficient countermeasure.